The Plight of Older Workers: Labor Market Experience after Plant Closure in the Swiss Manufacturing Sector - Baumann, Isabel (Life Course Research and Social Policies, 2016)
Organizational Studies, Economic Sociology; Labor Economics; Industrial and Organizational Psychology